A disorder of colour perception associated with abnormal colour after-images: a defect of the primary visual cortex. Issue 4 (1st October 2001) - Chan, D; Crutch, S J; Warrington, E K
Abstract : A 64 year old woman with posterior cortical atrophy secondary to probable Alzheimer's disease is described. Her presenting symptom was of seeing objects as abnormally coloured after prior exposure to a coloured stimulus. Formal testing disclosed that the patient experienced colour after-images of abnormal latency, duration, and amplitude. The demonstration of prolonged colour after-images in a patient with a cortical disease process provides strong evidence that the generation of colour after-images is mediated at least in part by the visual cortex. A mechanism for the generation of colour after-images is proposed in which abnormal prolongation of the images results from excessive rebound inhibition of previously excited wavelength selective neurons in V1. This may occur as a consequence of the relative sparing of inhibitory interneurons in V1 in the context of the degeneration of excitatory neurons that occurs in Alzheimer's disease.